Evaluation of the synthetic sex pheromone of the obscure mealybug, Pseudococcus viburni, as an attractant to conspecific males, and to females of the parasitoid Acerophagus maculipennis. Issue 2 (3rd October 2015) - Charles, John G.; Bell, Vaughn A.; Hall, Alistair J.; Suckling, D. Maxwell; Walker, James T.S.; Cole, Lyn M.; Shaw, Peter W.; Wallis, D. Roger; Millar, Jocelyn G.
Abstract The obscure mealybug, Pseudococcus viburni (Signoret) (Hemiptera: Pseudococcidae), is a cosmopolitan pest. In New Zealand, recently introduced management tools include the host‐specific parasitoid Acerophagus maculipennis (Mercet) (Hymenoptera: Encyrtidae) established in 2001, and pheromone‐baited monitoring traps available since 2005. Red delta traps baited with rubber septum lures impregnated with 4.0 μg of the mealybug synthetic sex pheromone, placed in apple orchards in Hawke's Bay and Nelson, trapped both male P. viburni and female A. maculipennis. Two generations of both species per year were discernible, but numbers were low in spring and parasitoids were not trapped during winter (June to September). Male P. viburni catches reached a plateau at a pheromone dose of ca. 1.0 μg per lure but numbers of A. maculipennis per trap increased up to 100 μg per lure, the maximum dose tested. A mathematical model showed that the lures had a half‐life of about 7.4 days and were most attractive to P. viburni with a dose of 0.19 μg, and that the trap effectiveness decreased rapidly once the release rate dropped below the optimum. The model also predicted that the initial pheromone dose should be increased from 0.19 to 5.41 μg per lure as the desired period of deployment increased from 0 to 9 weeks. A dose of 4.0 μg had an initial relative effectiveness of about 55%, reached peak effectiveness after about 5 weeks, and fell to 55% relative effectiveness again after about 8.3 weeks. We conclude that an initial pheromone load of 4.0 μg is appropriate for practical monitoring of P. viburni during the New Zealand summer. Future applications of the sex pheromone for managing the pest and parasitoid are discussed.